2009
DOI: 10.1108/13552540910979802
|View full text |Cite
|
Sign up to set email alerts
|

Use of wire bunch electrodes in electric discharge machining

Abstract: PurposeIn electrical discharge machining (EDM) process, the production of separate electrodes for rough, semi‐rough and finish machining of dies and moulds having complex surfaces, results in high cost and long lead‐time in manufacturing. The purpose of this paper is to describe the machining performance of electrodes formed by using copper wire bunches (WBs) positioned to conform the surface to be machined was experimentally and theoretically analyzed. In the study, the variations in the machining rate, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results showed that using such electrodes have facilitated the formation of a modified surface layer on the workpiece after EDM, with remarkable corrosion resistant properties. Kadir Dursun and Can Cogun [88] have investigated the performance of electrodes formed by using copper wire bunches (WBE s ). WBEs are proved to be economical as compared to conventional solid electrode.…”
Section: Electrode Manufacturing Using Some Other Techniquesmentioning
confidence: 99%
“…The results showed that using such electrodes have facilitated the formation of a modified surface layer on the workpiece after EDM, with remarkable corrosion resistant properties. Kadir Dursun and Can Cogun [88] have investigated the performance of electrodes formed by using copper wire bunches (WBE s ). WBEs are proved to be economical as compared to conventional solid electrode.…”
Section: Electrode Manufacturing Using Some Other Techniquesmentioning
confidence: 99%